Study on the Production Technology of Olive High Fiber Bread - HUANG Xiao-yu1; LIU Yu-hong; LI Jian-ke; JIN Feng; WU Gang-cheng; ZHANG Hui; JIN Qing-zhe; WANG Xing-guo (Liang you shipin ke-ji, 2023)
In order to improve the utilization of olive pomace, single-factor experiments were set up to investigate the effects of the amount of water and olive pomace addition on the quality of bread. Firstly, the basic components of olive pomace were determined. Secondly, the effects of water addition (50%, 52%, 54%, and 56%) on bread quality were investigated. After that, the influence of added olive pomace (5%, 10%, 15% and 20%) was also studied. The quality of bread was evaluated by taste, aroma and surface color, while physical properties were analyzed by the texture and the specific volume of bread. Results showed that the quality of bread was the best under the condition of adding 52% of moisture and 10% of olive pomace. With the addition of olive pomace, the specific volume of bread decreased, and the cohesion of bread decreased while the values of hardness, chewiness and adhesiveness increased. considered the appearance, quality, aroma and fiber content of bread, it was thought as the best to add 10% of olive pomace to the bread.